2019
DOI: 10.25248/reas.e1624.2019
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade do sono, apneia obstrutiva e autopercepção de saúde em idosos da comunidade

Abstract: Objetivo: Este estudo teve por objetivo avaliar a qualidade do sono, risco da Síndrome de Apneia Obstrutiva do Sono (SAOS) e autopercepção em saúde de idosos comunitários no interior do Rio Grande do Norte, Brasil. Métodos: Trata-se de estudo transversal, observacional com abordagem quantitativa, realizado nos meses de novembro e dezembro de 2015, com 61 idosos. Os participantes foram avaliados quanto autopercepção em saúde com instrumento, para avaliar a qualidade do sono foi usado o índice de qualidade de so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The study showed a statistically significant relationship between sleep and self-rated health (p=0.013): older adults participants who evaluated their own health as poor, very poor or regular had a higher prevalence of poor quality sleep and sleep disorders, when compared to the older adults who self-rated their health as excellent and good. National and international studies 21,[24][25] , also identified a relationship between poor quality sleep and poor self-assessment, corroborating the data obtained in the present study.…”
Section: /17supporting
confidence: 91%
See 2 more Smart Citations
“…The study showed a statistically significant relationship between sleep and self-rated health (p=0.013): older adults participants who evaluated their own health as poor, very poor or regular had a higher prevalence of poor quality sleep and sleep disorders, when compared to the older adults who self-rated their health as excellent and good. National and international studies 21,[24][25] , also identified a relationship between poor quality sleep and poor self-assessment, corroborating the data obtained in the present study.…”
Section: /17supporting
confidence: 91%
“…In addition, they are more affected by stressful situations and depressive symptoms when compared to men which impair night sleep. The feminization of old age may be accompanied by a higher prevalence of chronic health problems, including complaints related to night sleep [23][24] . In addition, hormonal conditions can also induce sleep problems in women, especially in the postmenopausal period 21 .…”
Section: /17mentioning
confidence: 99%
See 1 more Smart Citation